A GRASP for a resource-constrained scheduling problem. (14th June 2010) - Sirdey, Renaud; Carlier, Jacques; Nace, Dritan
This paper is devoted to the approximate resolution of a strongly NP-hard real world resource-constrained scheduling problem, which arises in relation to the operability of certain high availability real time distributed systems. We present a fast and pragmatic algorithm based on the GRASP metaheuristic and, building on previous research on exact resolution methods, extensive computational results demonstrating its practical ability to find solutions within a few percents to optimality on a wide spectrum of hard instances.